Implicature Analysis of Adel Al-Jubeir Political Interview on Yemen Campaign - Tri Pujiati; Abdulkhaleq Al-Rawafi; Darsita Suparno (Insaniyat : Journal of Islam and Humanities, 2020)
Politicians use their political interviews to convey their thoughts towards their nations or others. This study aims to analyze conversation analysis and implicature of maxims being flouted by Adel Al-Jubeir regarding the Yemeni campaign, which started on 26th of March 2014. The study uses descriptive qualitative method. The data were institutional talk (Interview) conducted by Adel Al-Jubeir as IE (interviewee) and the journalist Wolf Blitzer as IR (interviewer) in the CNN channel in Washington. The data were analyzed according to Clayman and Heritage (2002) for conversation analysis and implicature of maxim based on Grice (1975). The results show two linguistic evidences. First, in institutional talks, conversation consists of three components, namely, opening, content, and closing. The opening includes the introduction, the content includes the announcement of the beginning of the campaign interface on Yemen and the Iranian nuclear program and its threat to Saudi Arabia, and the closing includes complete pairs (greetings). Second, for implicature analysis, the results show that Al-Jubeir being over-informative, stating more than required, represented with 82% of the quantity. He made a speech that he believed to be false, unjustified, and untruthful replies, representing 100% in the scale of quality. He gave irrelevant meaning to respond other participants’ utterances, representing 65% of maxim of relation. He gave unclear and indirect replies, representing 77% of maxim of manner. Besides, Al-Jubeir cooperated with IR. In addition, it can be summarized that he applied both particularized conversational and general implicature on political interview with some violation of the maxims as well.